In Vitro Metabolic Stability Of Monocrotaline (MCT) and Heliotrine (HLT) in Rat Liver Microsome - Sasube, Laurensi M.; Luntungan, Aldian H. (Pascasarjana Unsrat, 2017)
The Pyrolizidine alkaloids (PAs) monocrotaline, and heliotrine chosen in our investigation are important as there are many reports if their occurrence as constituents of various food components as contaminated to cereal crops and herbal dietary supplements. These two PAs also belong to the two major classes of tumorigenic PAs, which is retronecine and heliotridine class. Although there is a sizable literature on monocrotaline and heliotrine, the information on the metabolism and toxicity of the important components of comfrey, is quite limited. Metabolic stability is defined as the percentage of parent compound lost over time in the presence of a metabolically active test system. The study in the compounds (MCT and HLT) stability is very important in order to investigate the profile of our compounds and as a foundation for further experiment. By understanding the metabolic stability of MCT and HLT in the early experiment will able to rank them in term of their rates of metabolism (slow or fast metabolism) and also to determine their half –life that will be benefit on define the incubation & sampling time. The aim of this research is to determine Metabolic Stability of Monocrotaline (MCT), and Heliotrine(HLT) in rat Liver Microsome. Rat liver microsome extraction and Higher Throughput Screening for Metabolic Stability. This research suggest that the two compounds of PAs Monocrotaline and Helitorine have demonstrated the stability in the liver microsome compare to propranolol . Their slowly metabolism in the liver or longer half-lives may explain their high properties to survive long enough to reach target organs and their metabolites to bind with tissue and macromolecule.Keywords: heliotrine, metabolic stability, monocrotaline